Individual Case Study & Report: Spotify - Hu, Xinyuan (International Journal of Global Economics and Management, 2024)
This article conducts market trend analysis on Spotify's mission statement, company profile, marketing orientation evaluation, and proposes Spotify's suggestions on segmentation, goals, positioning, marketing mix, customer journey mapping analysis, and detailed presentation of customer journey maps. I hope it can be helpful for Spotify's company marketing.